First time up : an insider's guide for new composition instructors - Dethier, Brock (Utah State University Press, 2005)
""First time up?""--An insider's friendly question from 1960s counter-culture-perfectly captures the spirit of this book. A short, supportive, practical guide for the first-time college composition instructor, the book is upbeat, wise but friendly, casual but knowledgeable (like the voice that may have introduced you to certain other firsts). With an experiential focus rather than a theoretical one, First Time Up will be a strong addition to the newcomer's professional library, and a great candidate for the TA practicum reading list. Dethier, author of The Composition Instru